Prediction of Self-Efficacy of Women with Gestational Diabetes Based on Coping Styles with Stress - Kordi, Masoumeh; Banaei Heravan, Mahsima (Advances in Nursing & Midwifery, 2020)
Abstract Introduction: Gestational diabetes (GA) is a common complication associated with perceived stress and self- efficacy effectiveness on the commitment to self-care behaviors. Therefore, this study aimed to predict the self- efficacy of women with gestational diabetes based on coping styles with stress. Methods: This study is a predictor correlation study that is done over 400 women with gestational diabetes attending to the clinic of hospitals related to Mashhad University of medical sciences and health centers in the city of Mashhad, Iran, in 2015. Data were collected by individual questionnaire, diabetic self- efficacy and coping styles questionnaire of Folkman and Lazarus. Descriptive Statistics performed data analysis, Spearman correlation coefficients test, Liner regressions model, and Multiple regression. A statistical significance was deemed present when the P-value was less than 0.05. Results: The results of Spearman correlation coefficients test showed a significant direct correlation between problem-based coping style and self-efficacy, (P < 0.0001 and r = 0.29); but, there was no significant linear relationship with emotive-based coping style (P = 0.105 and r = 0.08), and according to Liner regressions model, just the problem-based coping style is considered as a predictor variable of self-efficacy (P < 0.0001, β = 2.451, and F = 39.284). Conclusions: According to these findings, midwives can improve self-efficacy among women with gestational diabetes by encouraging them to apply problem-based coping styles with stress.